Retrograde Intramedullary Nail for Distal Femur Fracture, Through a Total Knee Arthroplasty. (August 2021) - Davis, Max; Wilson, Jenna; Weick, Jack; Hake, Mark
Abstract : Summary: Distal femur fractures are common in the elderly population. The risk of sustaining a distal femur fracture is increased with the presence of total knee arthroplasty components. Fixation with a retrograde intramedullary nail is a viable option for treatment of these injuries. This case-based video demonstrates the preoperative planning, techniques, and potential technical pitfalls to performing a retrograde intramedullary nail through a total knee arthroplasty in patients with a distal femur fracture.